Design of Improving The Quality of Human Resources Based on Islamic Schools in Anak Saleh Foundation, Malang City - Anwar Sa'dullah; Muhammad Fahmi Hidayatullah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The quality of human resources has become a vital aspect in the development of Islamic education institutions in particular. Almost every leading school has a design to improve the quality of human resources, bearing in mind that this aspect is the key to the birth of a quality generation. Learn from the Saleh Children's Foundation in improving the quality of human resources as a non-LPI general education institution to become one of the leading primary and early childhood education institutions in Indonesia. adi therein are Elementary Schools and Age Education. The two schools became role models of Islamic school-based management in line with the ideals of reform and independence. This study uses a descriptive qualitative research method with a case study approach with a multicase design. The results of this study are: improving the quality of teachers in early childhood education programs (PAUD) Anak Saleh through internal workshops and seminars which are held every Saturday. Its activities are based on output in the form of scientific work, and outcomes in the form of student and parent handbooks (news stories and prayers). While improving the quality of administrative and non-administrative education staff through collaborative activities with government agencies and non-government organizations.